Unlocking the Digital Realm: Exploring Perceptions and Practices in Educational Leadership - Enung Hasanah; Mohd Zailani Mohd Yusoff (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2024)
This study explores the perceptions, attitudes, and understanding of digital leadership practices among school principals and teachers, focusing on their potential impact on school performance. A qualitative research approach was employed, using semi-structured interviews with school principals and teachers to collect in-depth data on their views and experiences. Thematic analysis was conducted to identify recurring themes related to the role of digital leadership in school management. Key findings highlight that digital leadership enhances school management quality through fostering a culture of innovation, embracing change, setting clear goals, and effectively utilizing technology. Specifically, participants emphasized the importance of digital leadership in promoting creative problem-solving, facilitating adaptability to evolving educational needs, and ensuring goal alignment with school improvement initiatives. Additionally, digital leaders' ability to leverage technology for instructional and administrative tasks was crucial in supporting data-driven decision-making processes. The study concludes that digital leadership is pivotal in improving school performance by fostering innovation, adaptability, and clear strategic direction while emphasizing the importance of technological competence. These findings offer significant implications for educational management, advocating for leadership models that prioritize digital capabilities to meet the demands of modern education.